Adjunctive Chinese Herbal Products Therapy Reduces the Risk of Ischemic Stroke Among Patients With Rheumatoid Arthritis - Shen, Hsuan-Shu; Chiang, Jen-Huai; Hsiung, Nai-Huan (Frontiers in Pharmacology, 2020)
We performed a retrospective cohort study to investigate the association between the risk of ischemic stroke (IS) and the use of Chinese herbal products (CHP) in combination with western medicine (WM) among patients with rheumatoid arthritis (RA). The data were sourced from the registry for beneficiaries, inpatient and ambulatory care claims, and Registry for Catastrophic Illness from the National Health Insurance Research Database (NHIRD) in Taiwan between 1997 and 2011. Patients, who were newly diagnosed with RA between 1997 and 2010, were classified as the CHP group or non-CHP group depending on the presence of absence the adjunctive use of CHP following a diagnosis of RA. A total of 4,148 RA patients were in both the CHP and non-CHP groups after 1:1 matching. Patients in the CHP group had a significantly lower risk of IS compared to patients in the non-CHP group [adjusted hazard ratio (aHR): 0.67, 95% confidence interval (CI): 0.52–0.86]. In the CHP group, patients who used CHP for more than 30 days had a lower risk of IS than their counterparts (aHR: 0.61, 95% CI: 0.40–0.91). Gui-Zhi-Shao-Yao-Zhi-Mu-Tang, Shu-Jin-Huo-Xie-Tang, and Du-Huo-Ji-Sheng-Tang might be associated with a lower risk of IS. Finally, the use of CHP in combination with WM was associated with a decreased risk of IS in patients with RA, especially among those who had used CHP for more than 30 days. A further randomized control trial is required to clarify the casual relationship between these results.